AGE-OLD, SEXUAL AND SOMATOTYPOLOGICAL FEATURE OF SENTINEL INDEXES OF RHEOVASOGRAPHY OF SHIN FOR PRACTICALLY HEALTHY YOUTHS AND GIRLS OF PODILLYA - Ivanitsa, A.O. (World of Medicine and Biology, 2014)
The aim of this research was establishment of age-old, sexual and somatotypological features of sentinel indexes of shin rheovasography for practically healthy municipal youths and girls of Podolie. As a result of undertaken studies the set limits of confidence intervals and percentile scope of sentinel indexes of shin rheovasography are in general, different age-old and different after somatotype groups practically healthy youths and girls. In most cases age-old, sexual and somatotypological features of sentinel indexes of shin rheovasography both for youths and for girls touch time of descending part of rheovasography and time of the rapid blood filling.
Keywords: rheovasography of shin; time indices; healthy youths and girls; age; somatotype